결정질 실리콘 태양전지 표면 역 피라미드 구조의 특성 분석 - 양지웅(Jeewoong Yang); 배수현(Soohyun Bae); 박세진(Se Jin Park); 현지연(Ji Yeon Hyun); 강윤묵(Yoonmook Kang); 이해석(Hae-Seok Lee); 김동환(Donghwan Kim) (Current Photovoltaic Research, 2018)
To generate more current in crystalline silicon solar cells, surface texturing is adopted by reducing the surface reflection. Conventionally, random pyramid texturing by the wet chemical process is used for surface texturing in crystalline silicon solar cell. To achieve higher efficiency of solar cells, well ordered inverted pyramid texturing was introduced. Although its complicated process, superior properties such as lower reflectance and recombination velocity can be achieved by optimizing the process. In this study, we investigated optical and passivation properties of inverted pyramid texture. Lifetime, implied-Voc and reflectance were measured with different width and size of the texture. Also, effects of chemical rounding at the valley of the pyramid were observed.